Mito tecnicizzato, macchina mitologica e cultura di destra. Attraversamenti nel pensiero di Furio Jesi - Spina, Salvatore (Mechane, 2025)
In this paper I will analyze the relationship among technicalised myth, mythological machine and Right-Wing Culture in Furio Jesi’s Thought. The first part of the paper is dedicated to a short analysis of Germania segreta. The aim of this enquire is to underline the difference between “genuine myth” and “technicalised myth”, that Jesi borrows from Kerényi’s works. The second part aims to explore the gnoseological model of the ‘mythological machine’, that permits Jesi to overcome the difference proposed by Kerényi and to promote his specific theory of myth and mythology. At the end of the paper I will connect the notion of the mythological machine to the idea of Right-Wing Culture. The aim is to show how the gnoseological model of the mythological machine finds in the analysis of the Right-Wing Culture a special proving ground.